2000
DOI: 10.1074/jbc.275.5.3179
|View full text |Cite
|
Sign up to set email alerts
|

Exogenously Added Human Group X Secreted Phospholipase A2 but Not the Group IB, IIA, and V Enzymes Efficiently Release Arachidonic Acid from Adherent Mammalian Cells

Abstract: Mammalian secreted phospholipases A(2) (sPLA2s) comprise a group of at least eight enzymes, including the recently identified group X sPLA2. A bacterial expression system was developed to produce human group X sPLA2 (hGX). Inhibition studies show that the sPLA2 inhibitor LY311727 binds modestly more tightly to human group IIA sPLA2 than to hGX and that a pyrazole-based inhibitor of group IIA sPLA2 is much less active against hGX. The phospholipid head group preference of vesicle-bound hGX was determined. hGX b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
232
0
1

Year Published

2000
2000
2011
2011

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 210 publications
(253 citation statements)
references
References 72 publications
20
232
0
1
Order By: Relevance
“…By contrast, gIIaPLA 2 is measurable during cell activation because the preferential substrates for this secretory PLA 2 are phosphatidylserine and phosphatidylethanolamine, which are located at the inner leaflet of cell membrane (2)(3)(4). In this study, we also demonstrated that Naja naja naja PLA 2 and hXPLA 2 (37,38), both of which have greater PChydrolyzing activity than hVPLA 2 (36, 37), did not induce eosinophil adhesion. This is likely the result of the low affinity of each secretory PLA 2 for cell surface HSPG that mediate the internalization of secretory PLA 2 .…”
Section: Discussionsupporting
confidence: 47%
“…By contrast, gIIaPLA 2 is measurable during cell activation because the preferential substrates for this secretory PLA 2 are phosphatidylserine and phosphatidylethanolamine, which are located at the inner leaflet of cell membrane (2)(3)(4). In this study, we also demonstrated that Naja naja naja PLA 2 and hXPLA 2 (37,38), both of which have greater PChydrolyzing activity than hVPLA 2 (36, 37), did not induce eosinophil adhesion. This is likely the result of the low affinity of each secretory PLA 2 for cell surface HSPG that mediate the internalization of secretory PLA 2 .…”
Section: Discussionsupporting
confidence: 47%
“…In the present study no hydrolysis of surfactant PC was observed in sPLA 2 -IIA-treated mice. This is not surprising, since sPLA 2 -IIA, which bears basic residues resulting in positive charges of its interfacial binding surface, cannot bind well to PC vesicles, as described for PG (33,41,42).…”
Section: Discussionmentioning
confidence: 89%
“…For example, group V sPLA 2 is present in the macrophage-like cell line p388D1 and contributes a portion of the arachidonate released in response to lipopolysaccharide (6). Exogenous addition of groups V and X sPLA 2 s to a variety of mammalian cells leads to arachidonate release (7)(8)(9)(10). There is some evidence to suggest that the action of cPLA 2 -␣ is a prerequisite for sPLA 2 function in cells (11,12) and even for the vice versa scenario (13)(14)(15)), but such cross-talk between PLA 2 s remains poorly understood.…”
mentioning
confidence: 99%